School Administration According to Good Governance Affect Budgeting Management Under Samut Sakhon Primary Educational Service Area Office - Somboonpulperm, Uthaiwan; Indrangkura na Ayudthya , Patomporn; Intarasompun, Wichian (Journal of Modern Learning Development, 2024)
The objectives of this research is to study 1) the level of school administration according to good governance, 2) the level of budgeting management, and 3) the factors affect budgeting management of Samut Sakhon Primary Educational Service Area Office. The sample group used in this research consisted of 340 directors and teachers from a population of 2,273 people selected by stratified random sampling according to population proportion. The research tools is a questionnaire. Statistics used in data analysis include percentage, mean, standard deviation and Stepwise multiple regression analysis. The results of the research found that 1) the level of school administration according to good governance of Samut Sakhon Primary Educational Service Area Office Overall, the average is at a high level. 2) Level of budgeting management of Samut Sakhon Primary Educational Service Area Office Overall, the average is at a high level. 3) Motivational factors affecting budgeting management of Samut Sakhon Primary Educational Service Area Office Statistically significant at the .01 level with a multiple correlation coefficient of .807, the variable with the highest predictive influence. It has statistical significance at the .01 level and can predict the budgeting management factors. Under the Samut Sakhon Primary Educational Service Area Office, got 64.70 %.